2017
DOI: 10.4103/abr.abr_239_16
|View full text |Cite|
|
Sign up to set email alerts
|

Distribution of the Strains of Multidrug-resistant, Extensively Drug-resistant, and Pandrug-resistant Pseudomonas aeruginosa Isolates from Burn Patients

Abstract: Background:Pseudomonas aeruginosa is an opportunistic and Gram-negative pathogen that is used as the most important factor in burn wound infections, and due to the rapid acquisition of multidrug resistance (MDR), it causes high mortality rates in these sectors. Thus, diagnosis and assessment of antibiotic resistance patterns are very important in these patients. The aim of this study was to evaluate antibiotic resistance pattern and determining P. aeruginosa MDR.Materials and Methods:In this study, phenotypic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
6
20
2
Order By: Relevance
“…In total, these results indicate that the available choices for appropriate treatment of infection caused by these resistant isolates are currently limited. However, the data on colistin and polymyxin B used in our study were comparable to those in other studies [27][28][29] and, therefore, these are considered the antibiotics of choice against P. aeruginosa strains isolated from the patients with burn infections in this hospital. The presence of higher rates of resistance against the antimicrobial agents tested in the current study reflects the irrational and extensive administration of these antibiotics in our medical settings, which eventually resulted in the emergence of this resistance among bacterial isolates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In total, these results indicate that the available choices for appropriate treatment of infection caused by these resistant isolates are currently limited. However, the data on colistin and polymyxin B used in our study were comparable to those in other studies [27][28][29] and, therefore, these are considered the antibiotics of choice against P. aeruginosa strains isolated from the patients with burn infections in this hospital. The presence of higher rates of resistance against the antimicrobial agents tested in the current study reflects the irrational and extensive administration of these antibiotics in our medical settings, which eventually resulted in the emergence of this resistance among bacterial isolates.…”
Section: Discussionsupporting
confidence: 87%
“…Among those, 69 (43.7%) isolates were MBL producers based on the MBL E-test. This frequency was higher than in other studies, such as in one report from India 29 and two other recent studies from Iran 30,31 .…”
Section: Discussioncontrasting
confidence: 59%
“…In Iran, most studies have reported high resistance rates to amikacin and aztreonam and low resistance rate to levofloxacin and polymexin B (22,23), which might indicate the imprudent use of amikacin and aztreonam in Iran. In the present study, 95% of the P. aeruginosa isolates were MDR, which is similar to the results of studies performed by Safaei et al (24) and Mirsalehian et al (25). However, this rate is lower than the rates reported by Katvoravutthichai (21,26,27).…”
Section: Discussionsupporting
confidence: 91%
“…In this way, resistance to conventional antimicrobial agents in the market has been weekly reported at fungal species, leishmaniasis and pathogenic bacteria every week (9). Patients with cancer can undergo serious risk of infection as function these resistant infectious agents, in especial at the burn centers of many hospitals around the world (10). Therefore, research on the discovery of potential anticancer, antimicrobial (aseptic) and antifungal agent brings a clear vision for controlling and treating these diseases.…”
Section: Introductionmentioning
confidence: 99%